A novel way to statistically analyze morphologic changes in Dmp1-null osteocytes. (August 2014) - Ren, Y.; Lin, S.; Jing, Y.; Dechow, P. C.; Feng, Jian Q.
Abstract Recent studies have revealed multiple roles of osteocytes in bone metabolism. However, detailed analyses of the embedded osteocytes in bone structure are still limited because of the high mineral content around these cells. In this study, we developed an innovative technique, the "FITC-Imaris technique", which combines FITC ([2, 5]-Fluorescein isothiocyanate), confocal microscopy and Imaris software. With this method, we could not only visualize the 3-D morphology of embedded osteocytes, but more importantly, we were able to statistically quantitate the osteocyte structure in the cell surface area, total cell volume, and dendrite numbers. Furthermore, we made a side-by-side comparison of the new method with the acid-etched SEM imaging technique, a common imaging method for studies of osteocyte morphology with a much smaller cell depth (< 3 μm). Finally, we used the FITC-Imaris technique to show both the morphological and statistical differences in the osteocyte structure between the Dmp1-null mice (the osteomalacia model) and their age-matched control littermates. We expect that this newly developed technique will become a powerful tool to disclose more roles that osteocytes play in bone health and diseases.